Lgr4 promotes aerobic glycolysis and differentiation in osteoblasts via the canonical Wnt/β‐catenin pathway - Yang, Yu‐ying; Zhou, Yan‐man; Xu, Jing‐zun; Sun, Li‐hao; Tao, Bei; Wang, Wei‐qing; Wang, Ji‐qiu; Zhao, Hong‐yan; Liu, Jian‐min (Journal of bone and mineral research, 2021)
ABSTRACT Lgr4, a G‐protein‐coupled receptor, is associated with various physiological and pathological processes including oncogenesis, energy metabolism, and bone remodeling. However, whether Lgr4 is involved in osteoblasts' metabolism is not clear. Here we uncover that in preosteoblast cell line, lacking Lgr4 results in decreased osteogenic function along with reduced glucose consumption, glucose uptake, and lactate production in the presence of abundant oxygen, which is referred to as aerobic glycolysis. Activating canonical Wnt/β‐catenin signaling rescued the glycolytic dysfunction. Lgr4 promotes the expression of pyruvate dehydrogenase kinase 1 (pdk1) and is abolished by interfering canonical Wnt/β‐catenin signaling. Mice lacking Lgr4 specifically in osteoblasts (Lgr4osb−/−) exhibit decreased bone mass and strength due to reduced bone formation. Additionally, glycolysis of osteoblasts is impaired in Lgr4osb−/− mice. Our study reveals a novel function of Lgr4 in regulating the cellular metabolism of osteoblasts. © 2021 American Society for Bone and Mineral Research (ASBMR).